Pengembangan Media Video Animasi Menggunakan Capcut PadaMata Pelajaran IPAS Kelas IV Sekolah Dasar - Anggrayni, M.; Ratnawati, Ratnawati; Fransiska, Diana (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by students' difficulties in understanding science subjects. This difficulty is caused by the lack of using interesting learning media. Educators do not make use of available media in schools such as in focus, resulting in students becoming easily bored and less interested in paying attention to educators when explaining material which causes low student learning outcomes. To overcome these problems, efforts are needed to develop learning media in the form of Video Animation media. This study aims to produce a product or media in the form of animated video media using Capcut in class IV science subjects at SDN 03 Koto Besar that are valid, practical, and effective. The type of research used in this research is using the type of research R&D (Research and Development). Then the development model for this animated video media uses the ADDIE model which consists of five stages: Analyze. Design, Development, Implementation, and Evaluation. The results of the research on the development of animated video media using Capcut were stated to be very valid, based on the results obtained from the validator an average value of 84.72% was obtained in the very valid category, then for practical results an average value of 93.12% was categorized as very practical and for the results of the effectiveness of the completeness of the results of students obtained a value with an average of 88.89% categorized as very effective. Thus it can be concluded that animated video media using Capcut obtains very valid, very practical, and very effective values ??that educators can apply to make it easier during the learning process.